Blended Learning, Implementasi E-Learning Di Politeknik Negeri Balikpapan - Armin; Ali Abrar (JST (Jurnal Sains Terapan), 2015)
AbstractIn the document of Strategic Planning Year 2010 - 2014, Balikpapan State Polytechnic has set quality objectives to be achieved of which is to produce graduates who master the application of Information Technology. To achieve this goal, one of the programs that are launched is System Strengthening Program in Academic and Student Affairs with target availability of facilities gradually LMS and CMS. LMS (Learning Management System) is growing rapidly with the progress of ICT (Information and Communication Technology) in the form of the Electronic Learning System or e-Learning System. E-Learning is the educational system that uses an electronic application to support the development of teaching and learning activities with media computer networks, intranets and the internet either. With e-Learning allows the educational process without face to face and through the development of science to students can be conducted continuously. E-Learning models that will be implemented is Blended Learning, or learning method that combines e-Learning systems with conventional methods or face-to-face model.. Keywords: e-Learning, Blended Learning, Learning Managements System  Abstrak Dalam Rencana Strategis Tahun 2010 – 2014, Politeknik Negeri Balikpapan telah menetapkan sasaran mutu yang ingin dicapai di antaranya adalah menghasilkan lulusan yang menguasai aplikasi Teknologi Informasi. Untuk mencapai sasaran tersebut, salah satu program yang dicanangkan adalah Program Penguatan Sistem Akademik dan Kemahasiswaan dengan sasaran Tersedianya Fasilitas LMS dan CMS secara bertahap. LMS (Learning Management System)  berkembang pesat seiring kemajuan TIK (Teknologi Informasi dan Komunikasi) dalam bentuk Sistem Pembelajaran Secara Elektronik atau  e-Learning System. E-Learning adalah sistem pendidikan yang menggunakan aplikasi elektronik untuk mendukung pengembangan kegiatan belajar mengajar dengan media jaringan komputer, baik intranet maupun internet. Dengan e-Learning memungkinkan terjadinya proses pendidikan tanpa melalui tatap muka langsung dan pengembangan ilmu pengetahuan kepada mahasiswa bisa dilakukan secara terus menerus. Model e-Learning yang diimplementasikan adalah Blended Learning, atau metode   pembelajaran yang menggabungkan antara sistem e-Learning dengan metode konvensional atau tata muka (face-toface). Kata Kunci: e-Learning, Blended Learning, Learning Managements System